2021
DOI: 10.1186/s12936-021-03711-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dihydroartemisinin–piperaquine versus artemether–lumefantrine for treatment of uncomplicated Plasmodium falciparum malaria in Ugandan children: a systematic review and meta-analysis of randomized control trials

Abstract: Background The emergence of artemisinin resistance in Southeast Asia and Plasmodium falciparum kelch13 propeller gene mutations in sub-Saharan African pose the greatest threat to global efforts to control malaria. This is a critical concern in Uganda, where artemisinin-based combination therapy (ACT) is the first-line treatment for uncomplicated falciparum. The objective of this study was to compare the efficacy and safety of dihydroartemisinin–piperaquine (DHA–PQ) and artemether–lumefantrine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Consistently, the findings from a recent review showed that the appearance of gametocyte on day 1-14 and 29-42 was significantly lower in patients who were treated with AL than DHA-PQ (Assefa et al 2021). However, one previous study have reported that prolonged gametocytaemia after treatment could be an early sign of the occurrence drug resistance, which is also the case in the emergence of recrudescent infections (Delves et al 2013).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistently, the findings from a recent review showed that the appearance of gametocyte on day 1-14 and 29-42 was significantly lower in patients who were treated with AL than DHA-PQ (Assefa et al 2021). However, one previous study have reported that prolonged gametocytaemia after treatment could be an early sign of the occurrence drug resistance, which is also the case in the emergence of recrudescent infections (Delves et al 2013).…”
Section: Discussionsupporting
confidence: 67%
“…However, the activity of ACTs against mature gametocytes is limited [9]. Recently, studies have shown that the transmission reducing effect differs among ACTs (Abdulla et al 2016;Assefa et al 2021;Bousema et al 2006;Makanga 2014;Sawa et al 2013a;Yeka et al 2008). However, it is still unclear whether DHA-PQ and AL are the most appropriate choice for reducing community-wide transmission of P. falciparum in a place where malaria transmission intensity is high.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the e cacy and safety of the two ACT's also reported that cough, anorexia, diarrhea, and vomiting were the most common adverse events. In this review more patients from DHA-PQ treatment arm had cough than that of AL [34] and similarly, gastrointestinal adverse events were more frequent in patients who were treated with DHA-PQ in another study done in South East Asia and Africa [35][36][37][38].…”
Section: Discussionmentioning
confidence: 58%
“…A recent review on the efficacy and safety of the two ACT’s also reported that cough, anorexia, diarrhoea, and vomiting were the most common adverse events. In this review more patients from DHA-PQ treatment arm had cough than that of AL [ 49 ] and similarly, gastrointestinal adverse events were more frequent in patients who were treated with DHA-PQ in another study done in South East Asia and Africa [ 50 53 ]. Studies from the Thailand-Myanmar border [ 54 , 55 ] and elsewhere in Africa [ 56 58 ] have reported that DHA-PQ cause drug induced electrocardiographic QT prolongation, but a recent study also reported that the QT prolongation caused by piperaquine is not associated with an increased risk of sudden death [ 59 ].…”
Section: Discussionmentioning
confidence: 90%